Gross motor coordination in relation to weight status: a longitudinal study in children and pre-adolescents - Valentina Biino; Valentina Biino; Barbara Pellegrini; Barbara Pellegrini; Chiara Zoppirolli; Chiara Zoppirolli; Massimo Lanza; Federica Gilli; Matteo Giuriato; Federico Schena; Federico Schena (Frontiers Media S.A., 2023)
IntroductionGross Motor Coordination (GMC) is crucial for the adequate development of motor competence. Our purpose in this semi-longitudinal study was to evaluate the influence of BMI on GMC in children and pre-adolescents of both sexes, across school years (classes).MethodsWe evaluated 117 subjects (aged 8-13 years) belonging to three different cohorts for 4 consecutive years, providing data over 6 years (classes). GMC was assessed through the Körperkoordinationstest für Kinder (KTK) test. Class and weight status effects were then evaluated by dividing the subjects into a normal weight group and an overweight group based on their weight status.ResultsA significant increase across classes was found for BMI (p < 0.001) and KTK raw score (p < 0.001) and a decrease was found for KTK normalized score (MQ) (p = 0.043). Significantly lower MQ values were found for girls. Absolute GMC increased across the years and there was no difference between boys and girls. Correlations between GMC scores and BMI were negative and significant in 5 of 6 classes. It was confirmed that overweight subjects had lower MQ and RAW values than normal-weight subjects, with no class-by-weight status interaction.DiscussionThe level of competence and its development are strictly dependent on weight status during childhood and pre-adolescence. The present investigation suggests that the adequate development of GMC requires not only targeted physical education programs but also the promotion of healthy habits aimed at maintaining a normal weight status during childhood and pre-adolescence.